Letter to Jane Tolmach from S. Floyd Mori - S. Floyd Mori:::::: (1976)
This June 15, 1976 letter from Assemblyman S. Floyd Mori congratulates Jane Tolmach on her June 8 primary victory in the 36th District. Mori expressed confidence that she would also win the November general election and said he looked forward to working with her in the next legislative session. He closed by wishing her good luck.